Fenotipagem para estudos de estudos de tolerância à deficiência hídrica em eucalipto - Mendes, Hélio Sandoval Junqueira [UNESP] (2015)
The eucalyptus culture has great importance for the Brazilian forestry sector, being an excellent timber option for many purposes. Over recent years, the eucalyptus cultivation has expanded to regions with high levels of water deficit, imposing a new challenge for breeders and foresters that is recommendation of drought resistant genotypes. Thus, this work aim to evaluate the imposition of different ways of water stress on eucalypt, provided by types of pots and irrigation schemes combination, in order to advance in phenotyping methods in drought tolerance studies. Therefore, changes in Eucalyptus clones seeding physiological, biochemical and growth under different water availability conditions were studied. Three experiments were conducted: the first was conducted in cylindrical recipients of PVC under two irrigation regimes (R1 - alternate day and R2 - interruption of watering until visible wilting occurred) and three hybrids (H1 and H2 - Eucalyptus urophylla x E. tereticornis and H3 - hybrid E. urophylla x E. brassiana). Were evaluated in this experiment the following aspects: a) growth: height, stem diameter, number of leaves, leaf area, dry mass of leaves of stem + branches, root, aerial part, total and root/aerial part ratio; b) physiological: net assimilation rates, stomatal conductance, transpiration, water potential, membrane system damage, relative water content; c) biochemical: reducer and total soluble sugars content in leaves and roots. In the second experiment was monitored the survival of five clones of eucalypt (four hybrids of Eucalyptus grandis x E. urophylla - C1, C2, C3 and C5) and one clone of E. urophylla (C4): after watering interruption, in different sizes pots (3,6 L, 8 L, 25 L and 100 L). The gas exchange was evaluated and the hybrids death time delay counted. The third experiment was performed in two sizes pots (8 and 25 L), two irrigation schemes (the same as in the first experiment - R1 and R2) and ...